Effectiveness of Mindfulness Training on Experiential Avoidance, Self-Compassion, and Physiological Indices in Women with Breast Cancer - Mousapour, Mitra; Mirzaei, Hamidreza; Sadeghi, Fatemeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to examine the impact of mindfulness training on experiential avoidance, self-compassion, and certain physiological indices in women diagnosed with breast cancer. Method: This applied research was conducted as a quasi-experimental study with a pre-test, post-test, and control group design. The population included all women with stage 1 and 2 breast cancer who were under medical care after completing chemotherapy or radiotherapy at Shahid Tajrish Hospital in 2020-2021. A convenience sampling method was used to select 40 female breast cancer patients, who were equally divided into an experimental group (20 participants) and a control group (20 participants). Data were collected using the Neff’s Self-Compassion Scale (Neff, 2003), the Bond et al.’s Experiential Avoidance Questionnaire (2011), and physiological indices. Mindfulness training, based on the protocol by Lengacher et al. (2019), consisted of 8 sessions of 90 minutes each for the experimental group, while the control group received no intervention. Data were analyzed using covariance analysis. Findings: The results indicated that mindfulness training significantly increased self-compassion (F = 6.35, p < .05) and decreased experiential avoidance (F = 4.75, p < .05) in women with breast cancer. Additionally, the training significantly reduced cortisol levels (F = 7.38, p < .05), but did not have a significant effect on the concentrations of IL-6 (F = 0.83, p > .05) and CRP (F = 0.04, p > .05). Conclusion: Considering the current findings, it can be said that mindfulness training is effective in improving the psychological condition and reducing stress in women with breast cancer.